2019
DOI: 10.3390/ijerph16224433
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Electronic Cigarettes on Selected Antibacterial Properties of Saliva

Abstract: The aim of this study was to estimate changes in selected physicochemical properties of saliva collected from users of electronic cigarettes. Methods: The study population consisted of 120 patients (40 users of electronic cigarettes, 40 smokers of traditional cigarettes and 40 non-smokers). Laboratory tests included verification of saliva amount of lysozyme, lactoferrin and IgA. Results: Among e-cigarette users, statistically significant differences were observed in values of lysozyme and lactoferrin; however,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 39 publications
(65 reference statements)
0
29
0
1
Order By: Relevance
“…It is also possible that e-cigarettes modulate the oral microbiome indirectly. Indeed, they have been shown to affect levels of antimicrobial proteins and cytokines in saliva (Cichońska et al 2019; Ganesan et al 2020). In vitro, e-cigarette exposure increased proinflammatory cytokine production by premalignant and malignant cell lines, as well as accelerated infection by oral bacteria (Pushalkar et al 2020).…”
Section: Microbiological Evidencementioning
confidence: 99%
“…It is also possible that e-cigarettes modulate the oral microbiome indirectly. Indeed, they have been shown to affect levels of antimicrobial proteins and cytokines in saliva (Cichońska et al 2019; Ganesan et al 2020). In vitro, e-cigarette exposure increased proinflammatory cytokine production by premalignant and malignant cell lines, as well as accelerated infection by oral bacteria (Pushalkar et al 2020).…”
Section: Microbiological Evidencementioning
confidence: 99%
“…As recently described by Kumar and coworkers, E-liquids and their aerosols have also been shown to confer negative effects (Kumar et al, 2019). For example, antimicrobials lysozyme and immunoglobulin A are significantly decreased in the saliva of ECIG users (Cichoñska et al, 2019) as well as a pronounced adherence and biofilm growth of cariogenic pathogen Streptococcus mutans (Kim et al, 2018). Some data even suggest that ECIG-generated aerosol may be as dangerous (or potentially more dangerous) than conventional smoking (Jensen et al, 2015;Holliday et al, 2016;Yu et al, 2016).…”
Section: Introductionmentioning
confidence: 93%
“…Little information is available concerning the effects of ECIG-generated aerosol on the oral cavity and even less is known about the effects on the oral microbiota. In one study (Cichoñska et al, 2019), ECIG users were observed to have diminished levels of oral lysozyme and lactoferrin, suggesting that ECIG aerosol, like traditional smoke, diminishes the antimicrobial potential of saliva. Another study (Stewart et al, 2018) demonstrated that aerosolized E-liquid could possibly alter oral microbial populations.…”
Section: Introductionmentioning
confidence: 99%
“…Diverse factors may impact the whole oral environment and composition of saliva is among the most important. Factors that may affect saliva composition include genetic diseases such as Turner syndrome [ 19 ], general diseases or tobacco smoking and electronic cigarettes usage [ 20 , 21 ]. Electronic cigarettes are mechanical devices that can be divided into two categories: closed-system and open-system.…”
Section: Introductionmentioning
confidence: 99%
“…The cytotoxic effect is related to oxidative stress and increased concentration of proinflammatory cytokines [ 30 , 31 ]. Chemical compounds found in tobacco smoke and e-cigarettes liquids can dissolve in saliva, leading to disorders in its biochemical composition [ 21 , 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%